1970
DOI: 10.1021/ic50089a010
|View full text |Cite
|
Sign up to set email alerts
|

Crystal and molecular structure of trimeric phosphonitrilic isothiocyanate

Abstract: The crystal structure of trimeric phosphonitrilic isothiocyanate, I\T3Ps( NCS)6, has been determined by three-dimensional single-crystal %-ray studies. The compound crystallizes in the triclinic space group P i with a = 11.79 (3), b = 8.02 ( 2 ) , c = 10.31 (1) A, a = 96" 0' (30'), P = 99" 4' (30'), -/ = 97" 28' (33'1, and two molecules per unit cell. The calculated density is 1.70 (2) g c m P ; the experimental density is 1.62 ( 8 ) g ~m -~. The structure was solved from 1246 independent nonzero reflections c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
1991
1991

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The X-ray crystallographic analysis of (NPMe,), has been p r o m p t e d b y the recent structure determinations of the methylphosphazenes (NPMe,),-, (2)(3)(4)(5) i n addition to t h e previously k n o w n structure o f (NPMe,), (6). The structure o f (NPMe,), is also of interest in relation to those (22), NMe, (23), NCS (24), and 1/2[2,2'-0C6H4C6H40] (25).…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray crystallographic analysis of (NPMe,), has been p r o m p t e d b y the recent structure determinations of the methylphosphazenes (NPMe,),-, (2)(3)(4)(5) i n addition to t h e previously k n o w n structure o f (NPMe,), (6). The structure o f (NPMe,), is also of interest in relation to those (22), NMe, (23), NCS (24), and 1/2[2,2'-0C6H4C6H40] (25).…”
Section: Introductionmentioning
confidence: 99%
“…This difference is significant, but was also noticed in the structure of trimeric phosphonitrilic isothiocyanate (18). Hazel1 (19) has suggested that there is a relationship between the MRC angle and the N-C and C-S bond lengths.…”
Section: Resultsmentioning
confidence: 92%
“…A solution of the sodium salt of 2-(2-methoxyethoxy)ethanol was prepared from sodium hydride (2.70 g of a 60% dispersion in mineral oil, 0.0675 mol) and 2-(2methoxyethoxy) ethanol (8.11 g, 0.0676 mol) and was added to the polymer solution dropwise. The reaction mixture was stirred for 3 h at 25 °C to yield 21. The 31P NMR analysis indicated resonances at = -9 ppm for P(OCH2CH2OCH2CH2OCH3)2 units and at = -13 ppm for P(OCH2CH2OCH2CH2OCH3)Cl units.…”
Section: Characterization Of Thiourethane and Thioureamentioning
confidence: 99%